Upper third molar internal structural organization and semicircular canal morphology in Plio-Pleistocene South African cercopithecoids. Issue 95 (June 2016) - Beaudet, Amélie; Dumoncel, Jean; Thackeray, John Francis; Bruxelles, Laurent; Duployer, Benjamin; Tenailleau, Christophe; Bam, Lunga; Hoffman, Jakobus; de Beer, Frikkie; Braga, José
Abstract: Despite the abundance of cercopithecoids in the fossil record, especially in South Africa, and the recent development of morphometric approaches, uncertainties regarding the taxonomic identification of isolated cranio-dental specimens remain. Because cercopithecoids, nearly always found in stratigraphic association with hominin remains in Plio-Pleistocene deposits, are considered as sensitive ecological and chronological biomarkers, a significant effort should be made to clarify their palaeobiodiversity by assessing additional reliable morphological diagnostic criteria. Here we test the relevance of both molar crown internal structure and bony labyrinth morphology for discrimination of fossil cercopithecoid species. We use microtomographic-based 3D virtual imaging and quantitative analyses to investigate tooth endostructural organization and inner ear shape in 29 craniodental specimens from the South African sites of Kromdraai, Makapansgat, Sterkfontein and Swartkrans and provide the first detailed description of the internal structural condition characterizing this Plio-Pleistocene primate assemblage. Our preliminary results show that enamel-dentine junction morphology could be informative for discriminating highly autapomorphic taxa such as Theropithecus, while semicircular canal shape is tentatively proposed as an efficient criterion for diagnosing Dinopithecus ingens . Further research in virtual paleoprimatology may contribute to the identification of unassigned isolated fossil remains and shed new light on the internal craniodental morphology of extinct primate taxa.